Planning and Development Strategy of Pancer Door Beach Tourism Area in Pacitan City - Irfan Maulana Ashgaf; Lisa Dwi Wulandari (Jurnal Mahasiswa Jurusan Arsitektur, 2022)
Pacitan is a city nicknamed as "Paradise of Java" which has natural and abundant cultural wealth. Tourism is the mainstay of regional income. One of the beaches close to the city as the main destination is Pancer Door Beach. This area stretches wide but the condition of it doesn’t attract tourists because the diversity of potential both naturals, artificial and cultural are not optimal. This is a reference for researchers in knowing what are the potential of the Pancer Door Beach Tourism Area is that can be used as an important point in developing the area. This study uses qualitative research methods with SWOT analysis. The SWOT contains of the research identification which are then analysed in terms of strengths, opportunities, weaknesses and threats. From the SWOT analysis, a SWOT matrix appears. The SWOT matrix becomes the basis for finding a grand strategy. The grand strategy in this study is a combination between strong and weak potentials of the area for rapid and to overcome the slowdown in planning and development of Pancer Door Beach Tourism Area. Phenomena, interviews, research objects, and regulations as well as theoretical studies are the basis of developing the area on a micro-architectural scale. Keywords: 4A Tourism, Development, Planning, Potential